The direct formation of glycosyl thiols from reducing sugars allows one-pot protein glycoconjugation. - Bernardes, G; Gamblin, D; Davis, B (2006)
(Figure Presented) Sweet and easy: A one-pot method consisting of direct thionation (1) followed by thiol-mediated chemoselective ligation (2) can be used for site-selective protein glycosylation. This procedure, which uses the Lawesson reagent, has been shown to be fully compatible with unprotected sugars, the products of which can be directly used in a selenenylsulfide protein glycosylation strategy. © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.